ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) STUDI EMPIRIS PADA PERUSAHAAN YANG LISTED DI BEI - Andre Yosua Maruli Sirait; Primsa Bangun (Universitas Kristen Krida Wacana, 2013)
AbstractCorporate social responsibility disclosure is a process to communicate information about financial and non financial subject, related to the company’s activities to the environment and social environment in the annual report. The more company gives contribution to the environment, the better company’s image in public’s view. The sample used in this study was 25 of non financial companies listed on the Indonesia Stock Exchange (IDX) period 2009-2011. The purpose of this research was to analyze the influence of company size, profitability, leverage, and environmental performance on corporate social responsibility disclosure. The results of the research showed that the size firm, profitability, leverage, and environmental performance simultaneously influence on corporate social responsibility disclosure. Results of this study also showed that the significant positive effect of company size, the significant positive effect of profitability, and the significant negative effect of environmental performance on corporate social responsibility disclosure, while the leverage has no effect on the corporate social responsibility disclosure.Keywords:Corporate Social Responsibility Disclosure, Company Size, Profitability, Leverage, Environmental Performance